AETIOLOGICAL FACTORS OF NON-TRAUMATIC DUODENAL PERFORATION - Khan, Muhammad Siddique; Zeb, Junaid; Ahmad, Ashfaq; Zaman, Amer (Pakistan Journal of Physiology, 2017)
Background: Each year peptic ulcer disease affects 4 million people around the world. Perforation of the duodenum due to peptic ulcer remains a considerable medical problem causing high morbidity and mortality. This study aimed to determine the major aetiological factors of non-traumatic duodenal perforations. Methods: It was a cross-sectional study carried out in Surgical ‘B’ Unit, Ayub Teaching Hospital, Abbottabad, Pakistan from 15th Jun 2012 to 15th May 2015. One hundred and eighty-six patients were recruited for the study. Data was collected and analysed on SPSS-23. Results: Mean age of the study participants was 48.4±7.14 years. Male to female ratio was 3:5. The main causative agent was H. pylori (54.30%), 22.04% were smokers, 6.99% had history of using NSAIDS, and 31 (16.67%) patients had more than one causative factor. There was strong association found between age groups and socio-economic status (p=0.004), and literacy level of the respondents (p=0.003). Conclusion: Non-perforated duodenal ulcers are significantly associated with middle-aged people, low socioeconomic status, NSAIDS, smoking, and H. pylori. Pak J Physiol 2017;13(1):19–21.